Realities of American foreign policy - Kennan, George F. (Princeton, 1954)
THE LECTURES published in this volume were delivered as the Stafford Little Lecture Series at Princeton University in March 1954. I was at that time enjoying the privileges of membership in The Institute for Advanced Study in Princeton, privileges which made it possible for me to devote myself to this, and other, academic tasks. In presenting these lectures to the public I would like to express my appreciation to The Rockefeller Founda tion and The Institute for Advanced Study, whose assistance has made possible this pres ent period of academic retirement.